A Proposal for a Western Pacific Union (WPU). (3rd July 2021) - Shinichi, Kitaoka
Abstract : The concept of a Free and Open Indo-Pacific (FOIP) is taking firm hold as a new core vision of Japan's foreign policy. It has been endorsed at the US-Japan and Group of Seven (G7) summits. So far, however, there has not been sufficient discussion about specific approaches to promote it. In particular, the discussion on Southeast Asia, the region where the Pacific Ocean and the Indian Ocean meet, has been insufficient. Should Southeast Asia come under the influence of China, the significance of FOIP would be halved. This article proposes the establishment of a Western Pacific Union (WPU) at the heart of FOIP as a loose regional association by grouping the Western Pacific countries including Japan, major Southeast Asian countries (Indonesia, the Philippines, and Viet Nam), Australia and Pacific Island Countries. The proposed WPU aims to contribute to the regional and world's peace and prosperity, while not confronting China, by upholding the principles of freedom, democracy, and the rule of law.